The Effect of Antioxidants on Post-Thawed Angora Goat (Capra hircus ancryrensis) Sperm Parameters, Lipid Peroxidation, and Antioxidant Activities. - Tuncer, Purhan Barbaros; Bucak, Mustafa Numan; Sariozkan, Serpil; Sakin, Fatih; Atessahin, Ahmet; Kulaksiz, Recai; Cevik, Mesut (Soc Study Reproduction, 2010)
[Abstract Not Available]
43rd Annual Meeting of the Society-for-the-Study-of-Reproduction -- JUL 31-AUG 03, 2010 -- Milwaukee, WI